Results for the shallow structure of the broader region of Chania by HVSR measurements of ambient noise and their validation using simulation of ambient noise and independent geological information. - Papadopoulos, I.; Papazachos, C.; Savvaidis, A.; Theodoulidis, N.; Vallianatos, F.; Tsourlos, P. (Bulletin of the Geological Society of Greece, 2013)
The city of Chania is located at the Western-North part of the island of Crete. It is mostly built over Neogene sediments of unknown thickness. In the southern part of the city the Chania basin is developed, filled mainly by Quaternary deposits overlying the deep Neogene sediments. In this complex geological setting, we conducted over 200 single station measurements of ambient noise, aiming to estimate the predominant frequency of the subsurface formations. The obtained results for the HVSR data show a different behavior between sites located on Neogene and Quaternary deposits. In general, Neogene sediments show a single peak at low frequencies (below 1Hz, typically in the range 0.4-0.6Hz), indicating a very thick layer overlying the bedrock (Trypalion and Plattenkalk limestones). On the other hand, measurements at Quaternary deposits show two peaks, with the first one similar to the Neogene formations, while the second one is identified at higher frequencies, typically ~0.8-4.0 Hz. Simulation of ambient noise 1-D models show a good correlation between the experimental and theoretical HVSR curves, especially when the initial model consists of two layers (typically Neogene sediments overlying high-velocity bedrock formations) with a clear identification of the lower frequency HVSR peak, while for three layered models (typically Quaternary sediments and underlying softer Neogene and Neogene/bedrock high-velocity formations) results are more complicated, although both HVSR frequencies can be partly reconstructed.